2015
DOI: 10.1039/c5ra07932b
|View full text |Cite
|
Sign up to set email alerts
|

Large d33and enhanced ferroelectric/dielectric properties of poly(vinylidene fluoride)-based composites filled with Pb(Zr0.52Ti0.48)O3nanofibers

Abstract: Pb(Zr 0.52 Ti 0.48 )O 3 (PZT) nanofibers with diameter of 150~200 nm are prepared via electrospinning and used as dielectric fillers in Poly(vinylidene fluoride) (PVDF)-based composite films. Highly flexible polymer composite films are fabricated with a solution cast method. Enhanced dielectric constants are obtained at low volume fraction of PZT nanofibers. The orientation of PZT nanofibers perpendicular to the external electric field gives rise to improved dielectric breakdown strength. A subsequent uniaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 42 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…The piezoelectric coefficient (d 33 ) obtained for hybrid nanocomposite films was 30.6 pC/N, which is lesser than that of electrospun pure PNFs (30–57 pC/N). Large piezoelectric coefficients in electrospun PNFs are due to the improvement in electroactive phases, surface area, uniformity, and continuity of fibers .…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric coefficient (d 33 ) obtained for hybrid nanocomposite films was 30.6 pC/N, which is lesser than that of electrospun pure PNFs (30–57 pC/N). Large piezoelectric coefficients in electrospun PNFs are due to the improvement in electroactive phases, surface area, uniformity, and continuity of fibers .…”
Section: Introductionmentioning
confidence: 99%
“…For the nanocomposite filled with randomly distributed nanoparticles, the breakdown strength first increases and then decreases with the increase of V f , exhibiting a maximal breakdown strength of 1.05 times that of the pure matrix value at V f of 3%, as shown in Figure a. For the nanocomposite filled with parallel nanofibers displayed in Figure b, the breakdown strength exhibits a maximum of 1.15 times that of the pure matrix value when V f is 3% too. However, for the nanocomposite filled with parallel nanosheets shown in Figure c, the breakdown strength of the nanocomposite is enhanced in a broad range of V f , exhibiting a maximum around 1.4 times that of the pure matrix value at V f of 10%.…”
mentioning
confidence: 85%
“…For the last three of above five nanocomposites, there have been numerous experimental investigations on the breakdown strength enhancement as function of the volume fraction of the nanofillers ( V f ). Figure a–c list the experimental measured breakdown strengths for three types of microstructures with different V f , compared with the simulation results in this work. For the nanocomposite filled with randomly distributed nanoparticles, the breakdown strength first increases and then decreases with the increase of V f , exhibiting a maximal breakdown strength of 1.05 times that of the pure matrix value at V f of 3%, as shown in Figure a.…”
mentioning
confidence: 93%
“…[8][9][10][11][12][13][14][15][16][17] In the past, many authors, including our group have reported lead-based materials for suitable pressure sensors in the low and high-pressure range, where a signicant change in dielectric constant, piezoelectric coefficient and capacitive reactance was observed as a function of pressure. [1][2][3][5][6][7]13,[18][19][20][21][22][23][24][25][26] However, the effect of pressure on change in dielectric constant was not as signicant that it can be realized for real high-pressure sensor devices. Another drawback was the linearity in dielectric constant as a function of pressure.…”
Section: Introductionmentioning
confidence: 99%